ANALISIS SPASIAL DAYA DUKUNG LAHAN DAN PERTUMBUHAN PERMUKIMAN DI KECAMATAN SIRIMAU - Lasaiba, Mohammad Amin; Ansiska, Paisal; Tetelepta, Edward Gland (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2024)
Population growth and urbanization pose challenges in maintaining sufficient land carrying capacity. This research aims to analyze land carrying capacity and urban development in Sirimau District, Ambon City. Data collection methods involve direct observation and document collection. Data analysis utilizes a quantitative descriptive approach and spatial analysis with overlays of relevant parameters. The results show that the most significant growth occurs in Batu Merah Village. Land carrying capacity calculations reveal an average decrease in residential land carrying capacity. In 2022, Ahusen Village, Rijali Village, and Galala Village recorded a decrease in land carrying capacity below 1, indicating that these areas can no longer accommodate the population residing there. This suggests that population pressure and unchecked urban growth negatively impact land carrying capacity. Sustainable management measures, such as prudent urban spatial planning, protection of green areas, and appropriate infrastructure development, must be implemented.